2024
DOI: 10.1037/cfp0000222
|View full text |Cite
|
Sign up to set email alerts
|

It’s not us, it’s COVID: Individual and relational stress among Latine couples early in the pandemic.

Abstract: The COVID-19 pandemic has profoundly altered life in the United States, especially for ethnic and racial minority communities who are disproportionately affected by the virus. In this descriptive study, we sought to understand how mixed-gender Latine couples in the U.S. are functioning both dyadically and individually, in addition to identifying aspects of their unique experience during the early stages of the pandemic. We administered an online survey to 146 participants (67 mixed-sex dyads and 12 individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Women were left trapped with their abusers and isolated from social contact and support networks, exacerbating the situation [32,33,41]. This trend is not limited to South Asian families but extends to other ethnic families [42][43][44][45]. Furthermore, gender inequality, patriarchal social norms, stress, and financial crisis have all played a role in increasing domestic violence during COVID-19 [31,46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Women were left trapped with their abusers and isolated from social contact and support networks, exacerbating the situation [32,33,41]. This trend is not limited to South Asian families but extends to other ethnic families [42][43][44][45]. Furthermore, gender inequality, patriarchal social norms, stress, and financial crisis have all played a role in increasing domestic violence during COVID-19 [31,46,47].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the previous research also shows that in the face of adversity and challenge, some couples get closer and thrive (e.g., Marshall & Kuijer, 2017; see Prime et al, 2020). Some evidence from early in the pandemic shows that despite the overall strain, some relationships across international contexts have maintained their strength and partners have continued to support each other in effective ways (e.g., Balzarini et al, 2023; Fivecoat et al, 2024).…”
Section: The Present Studymentioning
confidence: 99%
“…Previous research has also found that Mexican American women’s emotional well-being and life satisfaction are nurtured by their supportive family relationships (Diaz & Bui, 2017). In the context of the COVID-19 pandemic, research with majority Latine couples in Arizona showed that most people felt close to their partner, supported, and satisfied in their relationships (Fivecoat et al, 2022). Importantly, for economically vulnerable and majority Latine families, increases in support from partners across the pandemic have been associated with higher levels of parenting engagement in child-focused activities and caregiving (He et al, 2021).…”
Section: Stress the Pandemic And Parent–child Interactionsmentioning
confidence: 99%